2021
DOI: 10.3389/fnut.2021.633738
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Humanized Diet Profile on Colonization Efficiency and Gut Microbial Diversity in Human Flora-Associated Mice

Abstract: Human flora-associated (HFA) mouse models allow us to design interventions for human disease research to test specific hypotheses and explore the complex commensal microbiome while avoiding the ethical limitations of using humans as models to directly study intestinal flora diseases. However, few studies have investigated the effect of a humanized diet profile (coarse-feed diet; CFD) on colonization efficiency and gut microbial diversity in HFA mice. We tested the colonization efficiency and gut microbial dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…71–73 Our previous study reported the effects of GTP interference on intestinal microflora and lipid metabolism in human flora-associated (HFA) mice. 17,32 Future research must consider how GTP dynamically modulates the gut microflora of HFA mice colonized with specific bacteriophages and host bacteria at different times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…71–73 Our previous study reported the effects of GTP interference on intestinal microflora and lipid metabolism in human flora-associated (HFA) mice. 17,32 Future research must consider how GTP dynamically modulates the gut microflora of HFA mice colonized with specific bacteriophages and host bacteria at different times.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the fecal 16S rRNA gene (the hypervariable V3–V4 region) was performed as previously described. 32 Briefly, the purified PCR products were pooled in equimolar amounts and paired-end sequenced using an Illumina Novaseq platform (Illumina, San Diego, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For a successful FMT experiment, fecal homogenate preparation was performed as in our previous study. 29 Before fecal homogenate preparation, the frozen samples were thawed in a thermostatic water bath at 37.5 °C for 10 minutes. Then, the thawed samples were suspended in phosphate-buffered saline (PBS, pH: 7.2-7.4), filtered step by step to remove undigested foods and particulate matters, washed, and resuspended using a vortex oscillator.…”
Section: Sample Collection and Materials Preparationmentioning
confidence: 99%
“…However, there are many challenges for the entry of exogenous microorganisms into the host, e.g., the gut environment (pH gradient, oxygen concentration) of the host (Evans et al 1988;Albenberg et al 2014), and rejection by the host immune system (Belkaid and Hand 2014). In addition, the host genotype and microbiota also affect the colonization capacity of foreign microorganisms (Dong et al 2021). Moreover, the gut microbiota of mice that were not treated with antibiotics was resistant to colonization by human fecal species, resulting in the reduced abundance and taxonomic diversity of transplanted fecal species .…”
Section: )mentioning
confidence: 99%